FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN WARGA DALAM PENERAPAN PHYSICAL DISTANCING DI TENGAH PANDEMI COVID-19 DI KECAMATAN MANDONGA TAHUN 2020 - Hepy Hepy; Hariati Lestari; Jusniar Rusli Afa (Endemis Journal, 2021)
Corona-virus is one of the main pathogens targeting the human respiratory system, prevention can be done by observing health protocols, one of them is maintaining physical distance (physical distancing). The implementation of maintaining physical distance (physical distancing) will not be optimal if it is not supported by citizens' compliance with the policy. Residents who do not comply with physical distancing can result in the number of Covid-19 cases continuing to increase. The aim of this research is to determine the factors related to citizen compliance in the application of Physical Distancing in the midst of the Covid-19 pandemic in Mandonga District in 2020.  This research is a quantitative analytic study with a cross sectional study approach.  The sample in this research used a proportional random sampling technique of 366 people.  Statistical test using chi square test.  Collected by questionnaire method using google form.  The results of this research indicate that there is a relationship between perceptions and residents' compliance in implementing physical distancing in the midst of the Covid-19 pandemic (p value = 0.002 < 0.05), there is a relationship between the role of health workers and residents' compliance in implementing physical distancing in the midst of the Covid-19 pandemic (p value = 0.006 < 0.05), and there is a relationship between family support and residents' compliance in implementing physical distancing in the midst of the Covid-19 pandemic (p value = 0.000 <0.05).  The conclusion is that there is a relationship between perceptions, the role of health workers, family support and residents' compliance in implementing physical distancing in the midst of the COVID-19 pandemic.